Strengthening Mathematics Education in Sri Lanka - World Bank (Washington, DC, 2014)
A well-informed and knowledgeable community is of vital importance for the economic and social development of a modem society. The knowledge and skills required for present day activities are much more complex than those required in the past. Today, many jobs require expert thinking and non-routine analytical skills, to identify and solve problems. Mathematics education focuses on developing a person's analytical and problem solving abilities. Thus a high quality mathematics education win ensure that students develop the skills that are essential not only in science and technology, but also in everyday life and the workplace. The government of Sri Lanka, recognizing the need for a high quality mathematics education has implemented several reforms in the recent past. Although the progress achieved is commendable, there is still room for improvement in certain important aspects of the learning teaching process. The main aim of the mathematics curriculum under these reforms is to create individuals who are able to think mathematically and apply mathematical knowledge effectively and responsibly in problem solving and decision making.